First report of donor cell–derived acute leukemia as a complication of umbilical cord blood transplantation - Fraser, Christopher J. (© 2005 by The American Society of Hematology, 2005)
Donor cell leukemia is a rare complication after allogeneic hematopoietic stem cell transplantation. A 12-month-old boy underwent unrelated donor umbilical cord blood transplant (UCBT) for refractory Langerhan's cell histiocytosis. Forty months after transplantation, he developed acute myeloid leukemia. Cytogenetic and molecular analysis confirmed donor cell origin. The Cord Blood Bank (CBB) contacted the donor's family and established that the child, now 7 years old, was healthy. This represents the first reported case of donor cell leukemia following UCBT. This case illustrates that donor cell leukemia is a rare but real event after UCBT as with other stem cell sources and highlights the need for CBBs to maintain linkage data between donors and recipients.